Pelatihan Pelaporan Online Menggunakan Aplikasi JAKI pada Karang Taruna RW. 07 Jagakarsa Jakarta Selatan - Purnamasari, Indah; Suwarisman, Achmad; Rachmat, Budi Kurniawan; Afriyanti, Iis (PASAI : Jurnal Pengabdian kepada Masyarakat, 2022)
Karang Taruna is a community organization that is useful as a forum and means of development for every young generation that grows and develops on the basis of awareness and social responsibility from, by and for the community, especially the younger generation in village/kelurahan areas, for example Karang Taruna RW 07 Jagakarsa, South Jakarta. There are lots of young people in RW 07 Jagakarsa who still don't know what the JAKI application is and how to use it because they don't understand the functions or benefits of the jaki application. The JAKI application has several functions, one of which is online reporting which can be used by the public to follow up on existing problems in the environment down to the relevant agency level. There are so many problems in the RW 07 environment that cannot be followed up on by the relevant agencies due to limited knowledge of the JAKI application, this has attracted the interest of RW 07 youth groups to take part in online reporting training using the JAKI application which aims to increase the ability and knowledge of RW 07 young people so that can be more active in the community and can help problems that exist in their environment. This training also provides a questionnaire that is useful for getting responses to the implementation of community service activities with a total of 12 respondents and there are 12 questions in the questionnaire that must be assessed by respondents. The results of the community service that has been carried out regarding online reporting training using the JAKI application at Karang Taruna RW 07 Jagakarsa, South Jakarta, the youth of RW 07 Jagakarsa have understood the benefits of the JAKI application and how to report it so that they become more active when there are problems in their environment to be able to help the community.